2013
DOI: 10.1097/01.mib.0000438135.88681.98
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Symptom Relapse in Collagenous Colitis After Withdrawal of Short-term Budesonide Therapy

Abstract: Our data demonstrate that a high stool frequency at baseline and a long duration of diarrhea are risk factors for symptom relapse in collagenous colitis, whereas budesonide maintenance therapy is a protective factor against symptom relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 19 publications
2
16
0
1
Order By: Relevance
“…This is in line with the observation that budesonide improves the consistency of the stool prior to a decrease in total stool numbers. These results are consistent with a recent multivariate analysis by Miehlke et al 11 based on pooled data from 123 patients in four randomised controlled trials that reported clinical remission after budesonide withdrawal. They found that a baseline stool frequency of more than five per day was associated with almost a fourfold increase in the risk of relapse after stopping budesonide therapy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in line with the observation that budesonide improves the consistency of the stool prior to a decrease in total stool numbers. These results are consistent with a recent multivariate analysis by Miehlke et al 11 based on pooled data from 123 patients in four randomised controlled trials that reported clinical remission after budesonide withdrawal. They found that a baseline stool frequency of more than five per day was associated with almost a fourfold increase in the risk of relapse after stopping budesonide therapy.…”
Section: Discussionsupporting
confidence: 91%
“… 9 Budesonide therapy is recommended by the European Microscopic Colitis Group (EMCG) as the treatment of choice for active disease. 1 However, after withdrawal of budesonide 61–88% of patients experience clinical relapse, 5 7 10 11 necessitating long-term intervention in patients with a chronic active course. Small studies (<50 patients) of up to 6 months’ duration investigating the efficacy of budesonide at a dose of 6 mg/day in maintaining remission have previously shown a significant benefit versus placebo.…”
Section: Introductionmentioning
confidence: 99%
“…However, 6-month maintenance therapy did not change the following disease course, as the relapse risk after withdrawal of 24 weeks’ maintenance treatment was similar to that observed after 6 weeks’ induction therapy, and the median time to clinical relapse was equal in the two groups (39 days versus 38 days) 115. A high stool frequency (more than five per day) at baseline and a long duration of diarrhea (>12 months) are risk factors for clinical relapse after withdrawal of short-term budesonide therapy in CC 117. In a recent randomized controlled trial, an even-lower dose of budesonide of 4.5 mg/day was found to be superior to placebo (clinical remission 61.4% versus 16.7%) during 12 months’ maintenance therapy 118.…”
Section: Therapymentioning
confidence: 52%
“…This may reduce relapse rates after budesonide discontinuation, which is quoted to be as high as 26%–82% 22. Relapse rates tend to be highest with the absence of budesonide maintenance treatment, baseline diarrhoea frequency >5/day and diarrhoea lasting longer than 12 months 24. This patient was not keen on maintenance budesonide treatment despite two induction courses and hence the need to escalate therapy.…”
Section: Discussionmentioning
confidence: 94%